2013
DOI: 10.1073/pnas.1301738110
|View full text |Cite
|
Sign up to set email alerts
|

Genetic circuitry of Survival motor neuron , the gene underlying spinal muscular atrophy

Abstract: The clinical severity of the neurodegenerative disorder spinal muscular atrophy (SMA) is dependent on the levels of functional Survival Motor Neuron (SMN) protein. Consequently, current strategies for developing treatments for SMA generally focus on augmenting SMN levels. To identify additional potential therapeutic avenues and achieve a greater understanding of SMN, we applied in vivo, in vitro, and in silico approaches to identify genetic and biochemical interactors of the Drosophila SMN homolog. We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 66 publications
1
35
0
Order By: Relevance
“…We also suggest that mutations of the U2AF large subunit gene uaf-1 might be protective modifiers of smn-1 loss-of-function mutants. Together with previous studies of other SMN modifiers, 18,[26][27][28][29][30]45 our findings should facilitate the understanding of SMN functions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We also suggest that mutations of the U2AF large subunit gene uaf-1 might be protective modifiers of smn-1 loss-of-function mutants. Together with previous studies of other SMN modifiers, 18,[26][27][28][29][30]45 our findings should facilitate the understanding of SMN functions.…”
Section: Discussionmentioning
confidence: 86%
“…27 Recently numerous interactors of SMN have been identified in Drosophila and C. elegans. [28][29][30] It remains unclear how these genes interact with Drosophila and C. elegans orthologs of SMN and whether these genes contribute to the defects of SMN-deficient mutants.…”
mentioning
confidence: 99%
“…Recent work has revealed that SYN-CRIP/hnRNPQ and Fragile X mental retardation protein (FMRP) are present in the same mRNP granule (Chen et al 2012), and loss of expression of FMRP or the ability of FMRP to interact with mRNA and polysomes can cause cases of Fragile X syndrome. Separate studies have also shown that SYNCRIP interacts with wild-type survival of motor neuron (SMN) protein but not the truncated or mutant forms found to cause spinal muscular atrophy (Rossoll et al 2002), and Syp genetically interacts with Smn mutations in vivo (Sen et al 2013). Understanding Syp function in the regulation of such diverse and complex targets may, therefore, provide new avenues for understanding the molecular basis of complex disease phenotypes and potentially lead to future therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic modifiers of the phenotypes arising from SMN deficiency in Drosophila and Caenorhabditis elegans have also been identified. 115,116 The identification of genetic modifiers and downstream targets of SMN, once validated and shown to improve phenotypes in established mouse models of SMA, will uncover a wide array of potential new drug targets for SMA to be directly assayed and screened. To date, however, most cell-based assays to identify novel SMA drugs have been designed to assess SMN2 expression.…”
Section: Therapeutic Approachesmentioning
confidence: 99%